(untitled) (London Journal of Research In Science: Natural and Formal, 2025)
Zero is the last number invented by humankind and a truly marvellous one. At first glance, its existence appears meaninglessit represents nothing. Yet, when placed before any digit, it changes nothing; when added after, it increases the number tenfold. Multiplying any number by zero results in zero; dividing zero by any number still yields zero; but dividing any number by zero leads to infinity. Zero symbolises the origin of the cosmosthe beginning of all things. While other numbers express the existence and transformation of matter, only zero represents the primordial origin of the universe and the beginning of phenomena. The cosmic origin is a state of non-material or immaterial existencenot absolute nothingness, but rather the foundational basis of all being. All things arise from such a base point, and that point is zero. Yet, this is a living, yin-yang zero. Let us begin at the beginning and reflect upon the profound significance of this number. The invention of information and knowledge by humanity may indeed serve to explain just thisperhaps it exists for precisely that reason. Expressed in the language of human-created information: zero is the beginning of the universe and of all things. Returning to zero symbolises balance and the perfect of human knowledge and information.